The effect of surgical and psychological stress on learning and memory function in aged C57BL/6 mice. (21st April 2016) - Zhang, C.; Li, C.; Xu, Z.; Zhao, S.; Li, P.; Cao, J.; Mi, W.
Highlights: Psychological stress is not a constitutive factor of POCD. Peripheral abdominal surgical stress leads to POCD in aged mice. AKT/mTOR pathway may involved in the development of POCD. Abstract: Postoperative cognitive dysfunction (POCD) is an important complication following major surgery and general anesthesia in older patients. However, the etiology of POCD remains largely to be determined. It is unknown how surgical stress and psychological stress affect the postoperative learning and memory function in geriatric patients. We therefore established a pre-clinical model in aged C57BL/6 mice and aimed to investigate the effects of surgical stress and psychological stress on learning and memory function and the possible roles of the protein kinase B/mammalian target of rapamycin (AKT/mTOR) pathway. The surgical stress was induced by abdominal surgery under local anesthesia, and the psychological stress was induced by a communication box. Cognitive functions and markers of the AKT/mTOR pathway were assessed at 1, 3 and 7 days following the stress. The impairments of learning and memory function existed for up to 7 days following surgical stress and surgical stress plus psychological stress, whereas the psychological stress did not affect the cognitive function alone or combined with surgical stress. Analysis of brain tissue revealed a significant involvement of the AKT/mTOR pathway in the impairment of cognition. These data suggested that surgical stress could induce cognitive impairment in aged mice and perioperative psychological stress is not a constitutive factor of POCD. The AKT/mTOR pathway is likely involved as one of the underlying mechanisms of the development of POCD.